2001
DOI: 10.1093/jnci/93.15.1133
|View full text |Cite
|
Sign up to set email alerts
|

Placental Characteristics and Reduced Risk of Maternal Breast Cancer

Abstract: Smaller placentas, maternal floor infarction of the placenta, and increasing blood pressure during pregnancy were associated with reduced maternal breast cancer. In the case of smaller placental diameter, the larger reduction observed with older age at first pregnancy suggests a process in which promotion of an existing lesion is blocked. Elucidating the mechanisms for these associations could provide clues to breast cancer prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 31 publications
2
87
1
Order By: Relevance
“…It has also been suggested that exposure to elevated androgen concentrations mediates the associations of prenatal factors with breast cancer risk (33,58). Siiteri (33) has speculated on a possible role for androgens in decreasing breast cancer risk among daughters born of preeclamptic pregnancies.…”
Section: Prominent Hypotheses To Explain Prenatal Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that exposure to elevated androgen concentrations mediates the associations of prenatal factors with breast cancer risk (33,58). Siiteri (33) has speculated on a possible role for androgens in decreasing breast cancer risk among daughters born of preeclamptic pregnancies.…”
Section: Prominent Hypotheses To Explain Prenatal Risk Factorsmentioning
confidence: 99%
“…Moreover, data from the Child Health and Development Studies show a marked reduction in breast cancer risk with elevated mean arterial pressure (175), and systolic blood pressure increases from mid-to late pregnancy below the diagnostic criterion for hypertension (58). Breast cancer risk also was independently associated with other markers of placental compromise, including maternal floor infarction and smaller placental size.…”
Section: Prenatal Risk Factors For Maternal Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Women who are diagnosed with pre-eclampsia in pregnancy may have a lower risk for breast cancer later in life compared to other parous women (Polednak and Janerich, 1983;Thompson et al, 1989;Troisi et al, 1998;Cohn et al, 2001;Vatten et al, 2002a, b) although a higher risk has also been reported (Paltiel et al, 2004). Women who develop pre-eclampsia tend to have higher levels of androgens and lower oestrogen and progesterone levels than women in normotensive pregnancies (Innes and Byers, 1999).…”
mentioning
confidence: 97%
“…Previous studies (Martin et al, 1986;Steier et al, 2002;Troisi et al, 2003;Atamer et al, 2004) indicate elevations in third trimester circulating maternal androgen concentrations in preeclampsia compared with uncomplicated pregnancies. Maternal exposure to elevated androgen concentrations has been hypothesised to mediate the protective influence of preeclampsia, perhaps by antagonising oestrogen's effects on breast epithelial cells (Innes and Byers, 1999;Cohn et al, 2001).…”
mentioning
confidence: 99%